Cidades inteligentes e sustentáveis: uma análise de Planos Diretores de municípios brasileiros selecionados - Felipe, Andressa Sarita (2020)
The application of the concepts of smart cities, sustainable cities and smart and sustainable cities emerged as an alternative to solve the adversities caused by the rapid urbanization process. Based on the association of intelligence, which concerns the integration between services and urban infrastructure with information and communication technologies, with sustainability, which corresponds to the contribution to the improvement of environmental protection, economic development, as well as equity and of social well-being, such cities provide a better functionality and effectiveness to urban systems in the local context. As urban planning is a means by such concepts can be applied, and also a guarantee that the city fulfills its social function through the application of its instruments through the Master Plan, the objective of this research is to identify the characteristics of smart and sustainable cities products presents in the Municipal Master Plans of some Brazilian cities. The methodology was based on the content analysis of the master plans of nine Brazilian cities, which differ in number of inhabitants, that is, they are small, medium or large, from different states, including the states of Pará, Paraíba, Mato Grosso do Sul, Goiás, Tocantins, Paraná, Bahia, Minas Gerais and São Paulo and are also from different Brazilian regions, the North, the Northeast, the Midwest, the Southeast or the South. The results point to divergences in the inclusion of the terms / keywords of the different categories of analysis by each of the municipal plans, it was also found that, in fact, the master plans contain passages that relate to the characteristics of Smart and Sustainable Cities, even if they do not use terms identical to those surveyed , but rather that they come closer in context and objectives. Thus, it is possible to conclude from the theoretical base explored and the analysis carried out that an alternative for urban planners, when building the Municipal Master Plans, is to incorporate the characteristics of Smart and Sustainable Cities, which can provide better functionality to urban systems, economic growth in the local context, and improvements related to people's quality of life.